Animals - Siede, George; Siede, George (Lincolnwood, Illinois Publications International, Ltd., 1996)
A children's book featuring labeled photographs of various animals, designed to introduce young readers to animal names and appearances.
Includes labeled photographs of a variety of common animals.
Keywords: Animals, literature, Picture books for children